Birth Defects in Singleton versus Multiple ART Births in Japan (2004–2008) - Ooki, Syuichi (Hindawi Publishing Corporation, 2011)
The purpose of the present study was to evaluate the relative risk (RR) of multiple births for birth defects after assisted reproductive technology (ART) using Japanese nationwide data from 2004 to 2008 with singletons as the reference group. In multiples compared to singletons, the percentage of birth defects per pregnancy were significantly higher (RR = 1.88, 95% confidence interval (CI) 1.60–2.13), the percentage of birth defects per live birth was not significantly higher (RR = 0.90, 95% CI 0.78–1.05 or RR = 0.94, 95% CI 0.81–1.10), and the early neonatal mortality rate was significantly higher (RR = 2.68, 95% CI 1.52–4.70 or RR = 2.80, 95% CI 1.60–4.92). The early neonatal mortality per 10,000 live births was slightly higher in ART (5.09) than in the general population (3.86). We concluded that the impact of birth defects after ART would be larger in families with multiples compared to families with singletons, since the mean number of children would be larger in the former.